Paramedics’ knowledge on intraosseous cannulation. - Balakrishnian M,; Johar MJ,; Ismail MS,; Ahmad Khaldun I,; Hamidah Y, (Penerbit UKM, 2013)
Access to an intravenous (IV) route is very crucial in emergency patients under resuscitation. The difficulty to access and administer fluid and drugs through intravenous will influence the outcome of patient. In case of unavailable of intravenous route, the alternative is intraosseous access. To date, there is no data available on the prevalence and pattern of intraosseous cannulation knowledge among emergency paramedics in the published literature from our country, even though the use of intraosseous cannulation for emergency patients is being practices. Therefore, the purpose of the present study was to determine the level of knowledge regarding intraosseous cannulation among emergency paramedics. The knowledge related to intraosseous cannulation among emergency paramedics was assessed through structured validated test questions. Fifteen paramedics participated in this study. Majorities of participants were male (86.6%). The age group ranged from 22 – 45 old years. The working experiences were from two to thirteen years. There was only 1 out of 15 participants who had scored 75%. The majority (10) scored 40% to 50%. This suggests that necessity in teaching of intraosseous cannulation among emergency paramedics needs to be emphasised.